Utilização dos jogos eletrônicos Euclidea e Pythagorea como ferramentas de aprendizagem na sala de aula virtual - SANTOS JUNIOR, Orivan Matos dos (2024)
Technological advances have revolutionized education, integrating digital media and electronic games as essential parts of learning. This study focuses on the relevance of electronic games as educational tools, especially in subjects such as mathematics, exploring their ability to engage students and facilitate the understanding of complex concepts. During the PIBEX 2020 project, with students from Escola Dr Inácio Koury Gabriel Neto (State Public School), located in the municipality of Castanhal, the importance of virtual classes was emphasized, highlighting the discussion of the contributions of the use of mathematical workshops, including use of electronic games such as Euclidea and Pythagorea. Conducting courses using these games highlights the power of these tools to promote engagement, personalization of learning and the development of cognitive skills. However, the importance of the teacher's role to effectively integrate these resources into the educational environment is highlighted.